Two-stage sintering of barium titanate ceramic and resulting characteristics - Chaisan W. (2014)
The potential of a two-stage sintering technique as a low-cost and simple ceramic fabrication to obtain highly dense and pure barium titanate ceramics with small grain size was demonstrated in this study. Effects of designed sintering conditions on phase formation, densification, microstructure, and electrical properties of the BaTiO3 ceramics were examined via X-ray diffraction (XRD), Archimedes method, scanning electron microscopy (SEM), dielectric and hysteresis measurements, respectively. It has been found that, under suitable two-stage sintering conditions, the dense perovskite BT ceramics with fine grain can be successfully achieved with good electrical properties.